"Morze i inne morza" Marka Krystiana Emanuela Baczewskiego - Cieślak, Tomasz (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2009)
The purpose of the study was the analysis of motif of sea in M. K. E. Baczewski’s lyrics volume Morze i inne morza (2006). This motif is not significant in Polish old and present-day poetry, but rather frequent. Morze i inne morza is based on many incoherent inspirations and associations of various pictures. For Baczewski, it is the way of conceptualization of the chaos of the universe, unknowable abyss of reality and the allegory of time and eternity.